Timed Up and Go and Five Times Sit to Stand Test among community- ambulant overweight and obese Saudi the elderly - Elkader, Samiha Mohamed Abd; Al-Shenqiti, Abdullah Mohamed; Tarek Mohamed El-Gohary (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the effect of Timed Up and Go category on the Five Times Sit to Stand Test, and to determine the role of recreational status on Timed Up and Go rating. Method: The descriptive, cross-sectional study was conducted between October 2018 and April 2019 at the College of Medical Rehabilitation Sciences, Taibah University, Madina, Saudi Arabia, and comprised community-ambulant retired overweight or obese subjects of either gender aged 60-69 years. Timed Up and Go, Five Times Sit to Stand Test and Single-Leg Stance Test were used to measure basic mobility, transitional skills and static balance respectively. Data was analysed using SPSS 23. Results: Of the 150 subjects, 108(72%) were males and 42(28%) were females. The overall mean age was 63.1±2.5 years and the mean body mass index was 29.6±3.8kg/m2. There were 46(31.5%) subjects who were freely mobile, 60(41.1%) who were mostly independent and 40(27.4%) who had variable mobility. Also, 36(24%) subjects were recreationally active, while 114(76%) were recreationally inactive. The freely mobile subjects managed to finish the Five Times Sit to Stand Test in less time than the other groups (p<0.05). The recreationally active subjects took significantly less time to finish the Timed Up and Go test compared to the inactive. Besides, the males had longer Single-Leg Stance Test timing than females (p<0.05). Conclusion: The elderly belonging to different Timed Up and Go mobility categories demonstrated variable Five Times Sit to Stand abilities, with the recreational mobility status significantly affecting the category.